Talent Management Literature Review - Singh, Rajesh Prettypal (Universitas Pelita Harapan, 2021)
The concept of talent management has attracted most of the researchers’ attention in the recent years. In today’s business environment, talent management becomes one important source of competitive advantage that creates value for all companies. In the current economic downturn, there is a high demand for talent in the organizations. The aim of this study is to examine talent management process in organizations. This article is based on a review of the academic and popular talent management literatures. The paper focused by clarifying the definitions and the importance of talent management and what factors influencing the growth of talent management.